Pepsico's green revolution: climate resilience boosts potato program - Talsma, Tiffany; Mai, Nguyen; Nguyen, Ly; Nguyen, Thuy; Basel, Ashleigh; Craparo, Alessandro; Nguyen, Kien Tri (2024)
Based on PepsiCo’s extensive grower data, the team developed climate-yield models tailored to supply chain specific needs, creating insights into climate risks and opportunities for potato production. These results were translated into actionable recommendations integrated into PepsiCo’s sustainability roadmaps. PepsiCo used the Climate Resilience Platform, an online tool developed from this project, to identify future climate risks and to better prioritize adaptation practices, thereby increasing its supply-chain resilience across 12 countries in its potato program.